2015
DOI: 10.1186/s12985-014-0234-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human papillomaviruses from formalin-fixed, paraffin-embedded pre-cancer and invasive cervical cancer specimens in Zambia: a cross-sectional study

Abstract: BackgroundThe most common human papillomavirus (HPV) genotypes isolated from cervical cancer in select African countries are HPV-16, HPV-18, HPV-35, and HPV-45, but the most common genotypes in Zambia are unknown. The overall objective of this study was to assess the potential impact of current HPV vaccines in preventing cervical cancer in Zambia, by determining the combined prevalence of HPV-16 and/or HPV-18 in invasive cervical cancer (ICC) and high-grade pre-cancer [cervical intraepithelial neoplasia 2 or 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
1
10
4
Order By: Relevance
“…We found no significant link between the histological lesions and the HPV carrier. In our study, the prevalence rate of precancerous lesions was significantly lower than that of most studies [13] [15] [21]. This could be explained by the size of our sample but especially by the quality of our samples; or other factors other than HPV such as bacteria, parasites, fungi, other virus, or simply other HPV genotypes that our detection kit could not characterize.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…We found no significant link between the histological lesions and the HPV carrier. In our study, the prevalence rate of precancerous lesions was significantly lower than that of most studies [13] [15] [21]. This could be explained by the size of our sample but especially by the quality of our samples; or other factors other than HPV such as bacteria, parasites, fungi, other virus, or simply other HPV genotypes that our detection kit could not characterize.…”
Section: Discussioncontrasting
confidence: 74%
“…Other studies have shown results that differ from ours [13]- [15]. In Zambia, a team [13] found a prevalence of moderate to severe dysplasia in 31% of the cases (65 HPV positive cases against 75 cases tested and 69 cases considered appropriate cases) (p < 0.001). However, this study in Zambia also used samples with similar storage period as ours and there was roughly the same number of samples.…”
Section: Discussioncontrasting
confidence: 59%
“…In the present study, HPV DNA was detected in 100% of the premalignant and malignant lesions that were present in the cervical biopsy specimens analyzed. This level of prevalence is similar to the levels reported by studies conducted in other countries that also examined paraffin-embedded samples graded as CIN I–III and cervical cancer: United States (95%), 13 Zambia (94%), 14 Ethiopia (93%), 15 and Pakistan (88%). 16 These findings reinforce the causal role of HPV infections in developing cervical malignancy 5 and the importance of archival biopsy samples as a source of material for studies related to the identification of HPV types.…”
Section: Introductionsupporting
confidence: 85%
“…The very large burden of cervical disease in HIV positive women reported here necessitates a multi-pronged prevention and control approach, including primary prevention with vaccination, secondary prevention with screening and treatment of precancerous lesions, and treatment of cervical cancers. This group has previously reported that approximately 70 % of cervical cancers at the University Teaching Hospital in Lusaka are positive for HPV-16 and/or HPV-18, the two HR-HPV genotypes in widely available vaccines [ 21 ]. In addition, immune responses to HPV vaccination among HIV positive women are reported to be generally robust [ 22 ].…”
Section: Discussionmentioning
confidence: 99%